2019
DOI: 10.1155/2019/5162687
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic Activity and Curative Role of Avenanthramides against the Growth of Ehrlich Solid Tumors in Mice

Abstract: Interest is growing in finding natural sources of effective antitumor agents that generate fewer side effects than conventional chemotherapeutic drugs. Avenanthramides (Avns) are such compounds; these phenolic molecules naturally occur in oats and have antioxidant, anti-inflammatory, and antiproliferative effects making them worthy of further research. The aim of this study is to characterise Avns' curative ability and antineoplastic activity on solid-form Ehrlich tumors. For the study, 75 female mice were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
84
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 82 publications
(113 citation statements)
references
References 52 publications
29
84
0
Order By: Relevance
“…In the immunohistochemical examination for PCNA and P53 proteins, a strong positive reaction in glomeruli and renal tubules were observed in the kidney sections of the Ehrlich carcinoma group according to Tousson et al and Eldaim et al who detected that Ehrlich tumor causes proliferation and apoptosis in renal tissues and induced strong positive expressions in Ki67, P53, and PCNA proteins in the female mice. Also, our results agree with Aldubayan et al who found that Ehrlich tumor‐induced higher expression of PCNA and KI67 proteins that observed in renal and hepatic tissues for mice. Finally, the treatment with VB17 in EAC bearing mice leads to decreased expression of PCNA and P53 proteins in renal tissue because it has anti‐proliferation and antiapoptotic effects; these results agree with Zhou et al reported that the improvement of amygdalin activated with β‐ d ‐glucosidase on HepG2 cells proliferation and apoptosis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the immunohistochemical examination for PCNA and P53 proteins, a strong positive reaction in glomeruli and renal tubules were observed in the kidney sections of the Ehrlich carcinoma group according to Tousson et al and Eldaim et al who detected that Ehrlich tumor causes proliferation and apoptosis in renal tissues and induced strong positive expressions in Ki67, P53, and PCNA proteins in the female mice. Also, our results agree with Aldubayan et al who found that Ehrlich tumor‐induced higher expression of PCNA and KI67 proteins that observed in renal and hepatic tissues for mice. Finally, the treatment with VB17 in EAC bearing mice leads to decreased expression of PCNA and P53 proteins in renal tissue because it has anti‐proliferation and antiapoptotic effects; these results agree with Zhou et al reported that the improvement of amygdalin activated with β‐ d ‐glucosidase on HepG2 cells proliferation and apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…According to numerous studies, plant ingredients and their extracts were used in anticancer, anti‐inflammation, reducing renal and hepatotoxicity, and treat many diseases . Vitamin B17 (VB17), amygdalin and formerly called laetrile is one of many nitrilosides which are natural cyanide containing substances, which is abundant in the seeds of Prunasins family, such as apricots, apples, almonds, peaches, and other rosaceous plants .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings agree with Yazar and Baydan and Abd El Raouf and Girgis who reported that ethephon induced hepatonephrotoxicity. PCNA is a DNA clamp that acts as a processivity factor for DNA polymerase δ in eukaryotic cells and is essential for replication; it plays an essential role in nucleic acid metabolism as a component of the replication and repair machinery . PCNA is a good marker for the regeneration and toxicity of the kidneys .…”
Section: Discussionmentioning
confidence: 99%
“…PCNA is a DNA clamp that acts as a processivity factor for DNA polymerase δ in eukaryotic cells and is essential for replication; it plays an essential role in nucleic acid metabolism as a component of the replication and repair machinery. 51 PCNA is a good marker for the regeneration and toxicity of the kidneys. 52,53 Also, a significant increase in PCNA expression in the kidney tissues of rats was intoxicated with ethephon.…”
Section: Costus Root Extract-ameliorated Ethephoninduced Kidney Dnamentioning
confidence: 99%